2005
DOI: 10.1152/ajpendo.00085.2005
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of the JAK2/STAT5 GH signaling pathway associated with increased CIS protein content in liver of pregnant mice

Abstract: (CIS) is considered a major mediator of this desensitization. Pregnancy is accompanied by an increment in GH circulating levels, which were reported to be associated with hepatic GH resistance, although the molecular mechanisms involved in this resistance are not clearly elucidated. We thus evaluated the JAK2/ STAT5b signaling pathway and its regulation by the suppressors of cytokine signaling (SOCS)/CIS family and the JAK2-interacting protein SH2-B␤ in pregnant mouse liver, a model with physiological prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
(101 reference statements)
0
8
0
1
Order By: Relevance
“…2002, Miquet et al . 2004, 2005). This implies that this signaling pathway would not be involved in the proliferative effect of overexpressed GH.…”
Section: Introductionmentioning
confidence: 99%
“…2002, Miquet et al . 2004, 2005). This implies that this signaling pathway would not be involved in the proliferative effect of overexpressed GH.…”
Section: Introductionmentioning
confidence: 99%
“…mGH was determined by RIA as already described [25]. mGH RIA kit was obtained through the National Hormone and Pituitary Program, NIDDK, NIH, USA.…”
Section: Mgh Determinationmentioning
confidence: 99%
“…Previous in vivo work has demonstrated that chronic exposure of rats to GH results in desensitization of the JAK2/STAT5b signaling pathway (22,44). This phenomenon has been attributed to GH-induced changes in the expression of the negative regulators of GH signaling, the SOCS, and the CIS proteins (18).…”
Section: Discussionmentioning
confidence: 99%